Metabolic history and metabolic fitness as drivers of anabolic heterogeneity in isogenic microbial populations. (9th September 2021) - Calabrese, Federica; Stryhanyuk, Hryhoriy; Moraru, Cristina; Schlömann, Michael; Wick, Lukas Y.; Richnow, Hans H.; Musat, Florin; Musat, Niculina
Summary: Microbial populations often display different degrees of heterogeneity in their substrate assimilation, that is, anabolic heterogeneity. It has been shown that nutrient limitations are a relevant trigger for this behaviour. Here we explore the dynamics of anabolic heterogeneity under nutrient replete conditions. We applied time‐resolved stable isotope probing and nanoscale secondary ion mass spectrometry to quantify substrate assimilation by individual cells of Pseudomonas putida, P . stutzeri and Thauera aromatica . Acetate and benzoate at different concentrations were used as substrates. Anabolic heterogeneity was quantified by the cumulative differentiation tendency index. We observed two major, opposing trends of anabolic heterogeneity over time. Most often, microbial populations started as highly heterogeneous, with heterogeneity decreasing by various degrees over time. The second, less frequently observed trend, saw microbial populations starting at low or very low heterogeneity, and remaining largely stable over time. We explain these trends as an interplay of metabolic history (e.g. former growth substrate or other nutrient limitations) and metabolic fitness (i.e. the fine‐tuning of metabolic pathways to process a defined growth substrate). Our results offer a new viewpoint on the intra‐population functional diversification often encountered in the environment, and suggests that some microbial populations may be intrinsically heterogeneous.